Load sharing for parallel three-phase inverters - Wang, Bo (2016)
With the development of society more swift, the power requirements are also gradually improved. Wireless inverters in parallel can achieve large capability and redundancy power supply. Parallel inverters not only reduce cost, but also improve the utilization rate. Power inverter modular in parallel is a useful method towards the development of high-power. Wireless parallel inverter power is researched and analyzed in this paper. The mathematical model of parallel inverters is analyzed in detail. An improved droop algorithm is proposed to realize wireless parallel operation. For this algorithm, active power and reactive power signals are included in the droop control, and the differential signals of active power and reactive power are included. The active power and reactive power signals are used to obtain better steady state performance. The differential signals are used to improve dynamic performance. The simulation results indicate that the wireless parallel inverters have good dynamic and steady state performances, the power sharing performance and circulating current restraining performance among inverter modules are also satisfactory by using the proposed algorithm.